The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

RivFishTIME: A global database of fish time‐series to study global change ecology in riverine systems - Lise Comte; Juan Carvajal‐Quintero; Pablo A. Tedesco; Xingli Giam; Ulrich Brose; Tibor Erős; Ana F. Filipe; Marie‐Josée Fortin; Katie Irving; Claire Jacquet; Stefano Larsen; Sapna Sharma; et al. (Global Ecology and Biogeography, 2021)
Motivation We compiled a global database of long‐term riverine fish surveys from 46 regional and national monitoring programmes and from individual academic research efforts, with which numerous basic and applied questions in ecology and global change research can be explored. Such spatially and temporally extensive datasets have been lacking for freshwater systems in comparison to terrestrial ones. Main types of variables contained The database includes 11,386 time‐series of riverine fish community catch data, including 646,270 species‐specific abundance records, together with metadata related to the geographical location and sampling methodology of each time‐series. Spatial location and grain The database contains 11,072 unique sampling locations (stream reach), spanning 19 countries, five biogeographical realms and 402 hydrographical basins world‐wide. Time period and grain The database encompasses the period 1951–2019. Each time‐series is composed of a minimum of two yearly surveys (mean = 8 years) and represents a minimum time span of 10 years (mean = 19 years). Major taxa and level of measurement The database includes 944 species of ray‐finned fishes (Class Actinopterygii). Software format csv. Main conclusion Our collective effort provides the most comprehensive long‐term community database of riverine fishes to date. This unique database should interest ecologists who seek to understand the impacts of human activities on riverine fish biodiversity and to model and predict how fish communities will respond to future environmental change. Together, we hope it will promote advances in macroecological research in the freshwater realm.

Identifying the source population of fish re-colonizing an arid-land stream following wildfire-induced extirpation using otolith microchemistry - James E. Whitney; Keith B. Gido; Skyler C. Hedden; G. L. Macpherson; Tyler J. Pilger; David L. Propst; Thomas F. Turner (Hydrobiologia, 2017)

River network architecture, genetic effective size and distributional patterns predict differences in genetic structure across species in a dryland stream fish community - Tyler J. Pilger; Keith B. Gido; David L. Propst; James E. Whitney; Thomas F. Turner (Molecular Ecology, 2017)
Dendritic ecological network ( DEN ) architecture can be a strong predictor of spatial genetic patterns in theoretical and simulation studies. Yet, interspecific differences in dispersal capabilities and distribution within the network may equally affect species’ genetic structuring. We characterized patterns of genetic variation from up to ten microsatellite loci for nine numerically dominant members of the upper Gila River fish community, New Mexico, USA . Using comparative landscape genetics, we evaluated the role of network architecture for structuring populations within species (pairwise F ST ) while explicitly accounting for intraspecific demographic influences on effective population size ( N e ). Five species exhibited patterns of connectivity and/or genetic diversity gradients that were predicted by network structure. These species were generally considered to be small‐bodied or habitat specialists. Spatial variation of N e was a strong predictor of pairwise F ST for two species, suggesting patterns of connectivity may also be influenced by genetic drift independent of network properties. Finally, two study species exhibited genetic patterns that were unexplained by network properties and appeared to be related to nonequilibrium processes. Properties of DENs shape community‐wide genetic structure but effects are modified by intrinsic traits and nonequilibrium processes. Further theoretical development of the DEN framework should account for such cases.

Comparative conservation genetics of protected endemic fishes in an arid-land riverscape - Tyler J. Pilger; Keith B. Gido; David L. Propst; James E. Whitney; Thomas F. Turner (Conservation Genetics, 2015)

Genetic analysis suggests high conservation value of peripheral populations of Chihuahau chub (Gila nigrescens) - Megan Osborne; Alana Sharp; Jerry Monzingo; David L. Propst; Thomas F. Turner (Conservation Genetics, 2012)

Spatial Variation in δ15N and δ13C Isotopes in the San Juan River, New Mexico and Utah: Implications for the Conservation of Native Fishes - Keith B. Gido; Nathan R. Franssen; David L. Propst (Environmental Biology of Fishes, 2006)

Spatial and temporal variation of fish communities in secondary channels of the San Juan River, New Mexico and Utah - Keith B. Gido; David L. Propst; Manuel C. Molles (Environmental Biology of Fishes, 1997)